Transgenic ipt tobacco overproducing cytokinins overaccumulates phenolic compounds during in vitro growth - Schnablová, Renáta; Synková, Helena; Vicánková, Anna; Burketová, Lenka; Eder, Josef; Cvikrová, Milena (Plant physiology and biochemistry, 2006)
We present evidence that overproduction of endogenous cytokinins (CK) caused stress response in non-rooting Pssu-ipt transgenic tobacco (Nicotiana tabacum L.) grown in vitro. It was demonstrated by overaccumulation of phenolic compounds, synthesis of pathogenesis related proteins (PR proteins), and increase in peroxidase (POD) activities. Immunolocalization of zeatin and also PR-1b protein on leaf cryo-sections proved their accumulation in all mesophyll cells of transgenic tobacco contrary to control non-transgenic plants. Intensive blue autofluorescence of phenolic compounds induced by UV in cross-sections of leaf midrib showed enhanced contents of phenolics in transgenic tobacco compared with controls, nevertheless, no significant difference between both plant types was found in leaf total lignin content. Transgenic plantlets exhibited higher peroxidase activities of both soluble and ionically bound fractions compared with controls. HPLC analysis of phenolic acids confirmed the increase in all phenolic acids in transgenic tobacco except for salicylic acid (SA). The effect of high phenolic content on rooting of transgenic tobacco is discussed.
Keywords: peroxidasy; Gene Expression Regulation, Enzymologic; Plant Roots; regulátory růstu rostlin; fenoly; Cytokinins; regulace genové exprese u rostlin; kořeny rostlin; cytokininy; kultivované buňky; Peroxidases; Plants, Genetically Modified; Nicotiana; Plant Growth Regulators; Gene Expression Regulation, Plant; regulace genové exprese enzymů; geneticky modifikované rostliny; Alkyl and Aryl Transferases; Cells, Cultured; Phenols; tabák; alkyltransferasy a aryltransferasy